Early transcriptome changes associated with western diet induced NASH in Ldlr−/− mice points to activation of hepatic macrophages and an acute phase response - Padiadpu, Jyothi; Spooner, Melinda H.; Li, Zhipeng; Newman, Nolan; Löhr, Christiane V.; Apperson, K. Denise; Dzutsev, Amiran; Trinchieri, Giorgio; Shulzhenko, Natalia; Morgun, Andrey; Jump, Donald B. (Frontiers in Nutrition, 2023)
Background: Nonalcoholic fatty liver disease (NAFLD) is a global health problem. Identifying early gene indicators contributing to the onset and progression of NAFLD has the potential to develop novel targets for early therapeutic intervention. We report on the early and late transcriptomic signatures of western diet (WD)-induced nonalcoholic steatohepatitis (NASH) in female and male Ldlr-/- mice, with time-points at 1 week and 40 weeks on the WD. Control Ldlr-/- mice were maintained on a low-fat diet (LFD) for 1 and 40 weeks. Methods: The approach included quantitation of anthropometric and hepatic histology markers of disease as well as the hepatic transcriptome. Results: Only mice fed the WD for 40 wks revealed evidence of NASH, i.e., hepatic steatosis and fibrosis. RNASeq transcriptome analysis, however, revealed multiple cell-specific changes in gene expression after 1 wk that persisted to 40 wks on the WD. These early markers of disease include induction of acute phase response (Saa1-2, Orm2), fibrosis (Col1A1, Col1A2, TGFβ) and NASH associated macrophage (NAM, i.e., Trem2 high, Mmp12 low). We also noted the induction of transcripts associated with metabolic syndrome, including Mmp12, Trem2, Gpnmb, Lgals3 and Lpl. Finally, one week of WD feeding was sufficient to significantly induce TNFα, a cytokine involved in both hepatic and systemic inflammation. Conclusion: This study revealed early onset changes in the hepatic transcriptome that develop well before any anthropometric or histological evidence of NASH and pointed to cell-specific targeting for the prevention of disease progression.